Pro JPA 2 in Java EE 8 An In-Depth Guide to Java Persistence APIs - Keith, Mike (Apress, 2018)
Learn to use the Java Persistence API (JPA) and other related APIs as found in the Java EE 8 platform from the perspective of one of the specification creators. A one-of-a-kind resource, this in-depth book provides both theoretical and practical coverage of JPA usage for experienced Java developers. Authors Mike Keith, Merrick Schincariol and Massimo Nardone take a hands-on approach, based on their wealth of experience and expertise, by giving examples to illustrate each concept of the API and showing how it is used in practice. The examples use a common model from an overarching sample application, giving you a context from which to start and helping you to understand the examples within an already familiar domain. After completing Pro JPA 2 in Java EE 8, you will have a full understanding of JPA and be able to successfully code applications using its annotations and APIs. The book also serves as an excellent reference guide. You will: Use the JPA in the context of enterprise applications Work with object relational mappings (ORMs), collection mappings and more Build complex enterprise Java applications that persist data long after the process terminates Connect to and persist data with a variety of databases, file formats, and more Use queries, including the Java Persistence Query Language (JPQL) Carry out advanced ORM, queries and XML mappings Package, deploy and test your Java persistence-enabled enterprise applications.